The Regulatory Responses to the Global Financial Crisis : Some Uncomfortable Questions - Claessens, Stijn (IMF Working Papers; Working Paper ;, 2014)
We identify current challenges for creating stable, yet efficient financial systems using lessons from recent and past crises. Reforms need to start from three tenets: adopting a system-wide perspective explicitly aimed at addressing market failures; understanding and incorporating into regulations agents' incentives so as to align them better with societies' goals; and acknowledging that risks of crises will always remain, in part due to (unknown) unknowns - be they tipping points, fault lines, or spillovers. Corresponding to these three tenets, specific areas for further reforms are identified. Policy makers need to resist, however, fine-tuning regulations: a 'do not harm' approach is often preferable. And as risks will remain, crisis management needs to be made an integral part of system design, not relegated to improvisation after the fact.